2017
DOI: 10.1016/j.stem.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A Quiescent Bcl11b High Stem Cell Population Is Required for Maintenance of the Mammary Gland

Abstract: Summary Stem cells in many tissues sustain themselves by entering a quiescent state to avoid genomic insults and to prevent exhaustion caused by excessive proliferation. In the mammary gland, the identity and characteristics of quiescent epithelial stem cells are not clear. Here, we identify a quiescent mammary epithelial cell population expressing high levels of Bcl11b and located at the interface between luminal and basal cells. Bcl11bhigh cells are enriched for cells that can regenerate mammary glands in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 60 publications
5
77
1
Order By: Relevance
“…The function of nuclear FOXO1 in other mammary epithelial cell types such as ER − body/luminal cells and mature ductal basal cells remains to be understood. Indeed, FOXO TFs are suggested to repress the cell cycle downstream of BCL11B, a critical regulator of basal cell quiescence in the mammary gland (Cai et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of nuclear FOXO1 in other mammary epithelial cell types such as ER − body/luminal cells and mature ductal basal cells remains to be understood. Indeed, FOXO TFs are suggested to repress the cell cycle downstream of BCL11B, a critical regulator of basal cell quiescence in the mammary gland (Cai et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Studies have since attempted to refine the identity of MaSCs. Accordingly, these studies leverage previously identified stem cell properties, such as expression of transcriptional regulators of ‘stemness’ (Chakrabarti et al, 2014; Junankar et al, 2015), stem cell-maintaining WNT pathway activity (de Visser et al, 2012; Plaks et al, 2013; van Amerongen et al, 2012; Wang et al, 2015), mesenchymal cell properties (Dravis et al, 2015; Guo et al, 2012), or markers of quiescence (Cai et al, 2016; dos Santos et al, 2013; Fu et al, 2017). However, no single, robust, pan-MaSC marker has emerged, suggestive of heterogeneity within the MaSC pool.…”
Section: Introductionmentioning
confidence: 90%
“…Conversely naïve T cells overexpressing Bcl11b manifest increased proliferation, most notably in the Th group (Ikawa et al, 2010; VanValkenburgh et al, 2011). Recently it has been found that Bcl11b induces mammary stem cells into the G0 cell cycle phase, entering quiescence (Cai et al, 2017). Similar to maintenance of mammary epithelium Bcl11b has an important role in epidermal stem cell maintenance and integrity as well as sphingolipid biosynthesis (Ganguli-Indra et al, 2009; Wang et al, 2012a; Bollag, 2013; Inoue et al, 2016).…”
Section: Other Rolesmentioning
confidence: 99%
“…Cai and colleagues now demonstrate that high levels of Bcl11b mark a quiescent stem cell population that has potent regenerative activity (2). In addition, the authors show that Bcl11b induces cells into G0 of the cell cycle and that loss of Bcl11b impairs normal mammary gland development.…”
mentioning
confidence: 99%
“…The existence of quiescent stem cells has been reported in many tissues, but until recently, such a stem cell has not been convincingly shown in the mammary gland. In a recent issue of Cell Stem Cell, Cai and colleagues [2017] reported the identification of a quiescent stem cell that expresses high levels of Bcl11b and is required for long-term maintenance of the mammary gland (2).…”
mentioning
confidence: 99%